Assessment of intra-tumoral karyotypic heterogeneity by interphase cytogenetics in paraffin wax sections. Issue 5 (October 1996) - Southern, S A; Herrington, C S
Abstract : Aim —To analyse the effect of sectioning on the assessment of karyotypic heterogeneity by interphase cytogenetics in paraffin wax embedded normal squamous epithelium and to apply the principles derived to invasive cervical carcinoma. Methods —Normal male (n = 5) and female (n = 5) squamous epithelia were hybridised with peri-centromeric repeat probes specific for chromosomes X (DXZ1) and 17 (D17Z1) individually and in combination to assess the effect of sectioning on mono-, di-, tri-, and tetrasomic populations. Section thickness, interobserver variation and variation between different areas of the epithelium were evaluated. Invasive squamous carcinomas of the cervix (n = 5) were then hybridised with the DXZ1 probe and intratumoral heterogeneity was assessed by comparison of signal distributions obtained from different areas. Results —The optimum section thickness for the assessment of normal epithelium was 6 μm. Variation in the expected signal number in the range 1-4 did not introduce artefactual heterogeneity at this section thickness. The sensitivity of this approach for the detection of minor subpopulations was calculated to be 13-16%, 17-18% and 10-11% for mono-, tri- and tetrasomic populations, respectively. Karyotypic heterogeneity was detected in two of the five tumours and, in one case where the populations where clustered morphologically, a minor population representing 18% was identified. Conclusions —Interphase cytogenetic analysis of sections from paraffin wax embedded material can be used for the detection of minor subpopulations in tumours. This approach will be of particular value in the assessment of the relation between human papillomavirus infection and tumour karyotype and in the analysis of intraepithelial neoplasia.